Effect of Brand Image, Price, and Quality Perceived by Consumers on Interest in Buying Wardah Cosmetics Products in Banda Aceh City - Farmiati, Josi; Ismail (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2021)
This research was conducted to investigate the effect of brand images, perceived price, and perceived quality of purchase intention consumers of Panin Bank Banda Aceh. Respondents in this research were all employees of Wardah Cosmetics at Banda Aceh which amounted to 100 responds (convenience sampling). The analysis model that used in this research was the multiple linear regression. Based on the regression results found that brand images, perceived price, and perceived quality positively affect to purchase intention of consumers of Wardah Cosmetics at Banda Aceh. Partially only two variables that significantly affected purchase intention, two variables were brand image and perceived quality (a = 0,05), while the perceived price has no significant effect on purchase intention.